Tumor-specific killer cells in paraneoplastic cerebellar degeneration - Albert, Matthew L.; Darnell, Jennifer C.; Bender, Armin; Francisco, Loise M.; Bhardwaj, Nina; Darnell, Robert B. (Nature Medicine, 1998)
Models for immune-mediated tumor regression in mice have defined an essential role for cytotoxic T lymphocytes (CTLs); however, naturally occurring tumor immunity in humans is poorly understood 1 . Patients with paraneoplastic cerebellar degeneration (PCD) provide an opportunity to explore the mechanisms underlying tumor immunity to breast and ovarian cancer. Although tumor immunity and autoimmune neuronal degeneration in PCD correlates with a specific antibody response to the tumor and brain antigen cdr2 2 , 3 , this humoral response has not been shown to be pathogenic 3 , 4 . Here we present evidence for a specific cellular immune response in PCD patients. We have detected expanded populations of MHC class I-restricted cdr2-specific CTLs in the blood of 3/3 HLA-A2.1 + PCD patients, providing the first description, to our knowledge, of tumor-specific CTLs using primary human cells in a simple recall assay. Cross-presentation of apoptotic cells by dendritic cells also led to a potent CTL response. These results indicate a model whereby immature dendritic cells that engulf apoptotic tumor cells can mature and migrate to draining lymph organs where they could induce a CTL response to tissue-restricted antigens. In PCD, peripheral activation of cdr2-specific CTLs is likely to contribute to the subsequent development of the autoimmune neuronal degeneration.